2021
DOI: 10.1111/jfbc.13615
|View full text |Cite
|
Sign up to set email alerts
|

Chlorogenic acid co‐administration abates tamoxifen‐mediated reproductive toxicities in male rats: An experimental approach

Abstract: Reports over the years have demonstrated toxic side effect-including reproductive toxicity-of tamoxifen (TAM), a drug of choice in the management of primary breast cancer. Chlorogenic acid (CGA), a dietary polyphenol, reportedly elicits beneficial pharmacological effects. However, the impact of CGA on TAM-associated reproductive toxicity is absent in the literature. We, therefore, experimented on CGA's effect and TAM-mediated reproductive toxicity in rats. Cohorts of rats were treated with TAM (50 mg/kg) or co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 105 publications
(111 reference statements)
0
20
0
Order By: Relevance
“…The stains were dissolved in distilled water and ethanol in a two to one (2:1) ratio for the investigation of sperm morphological alterations. Conversely, the viability of the spermatozoa was appraised by eosin (1%) and nigrosine (5%) stain in a solution containing 3% sodium citrate dehydrate following the established protocol of Wells and Awa (Wells & Awa, 1970) and as previously reported (Owumi, Anaikor, et al., 2021). For the assessment of sperm morphological status, 400 sperm cells were examined from each rat.…”
Section: Methodsmentioning
confidence: 99%
“…The stains were dissolved in distilled water and ethanol in a two to one (2:1) ratio for the investigation of sperm morphological alterations. Conversely, the viability of the spermatozoa was appraised by eosin (1%) and nigrosine (5%) stain in a solution containing 3% sodium citrate dehydrate following the established protocol of Wells and Awa (Wells & Awa, 1970) and as previously reported (Owumi, Anaikor, et al., 2021). For the assessment of sperm morphological status, 400 sperm cells were examined from each rat.…”
Section: Methodsmentioning
confidence: 99%
“…These results indicate that CGA was the main active component of EFEE in promoting spermatogenesis. Previous studies showed that CGA could increase the number of sperm in rat testis, moreover, CGA abated tamoxifen-mediated reproductive toxicities and improved the testosterone secretion and sperm motility in male rats ( Park and Han, 2013 ; Owumi et al, 2021 ). These studies indicate that CGA could promote the spermatogenesis, and our study was consistent with results above.…”
Section: Discussionmentioning
confidence: 93%
“…In our studies, we observed significant tor 1 (apaf-1), and activate caspase-9, which drives the activation of caspase-3, the executor of apoptosis. (Owumi, Anaikor, et al, 2021).…”
Section: Sod Dismutase Superoxide Anion Radical (Omentioning
confidence: 99%